Formulation and in Vitro, ex Vivo and in Vivo Evaluation of Elastic Liposomes for Transdermal Delivery of Ketorolac Tromethamine - Néstor Mendoza; David Quintanar; Luis Mendoza; Elizabeth Piñón; Guadalupe Nava; Adriana Ganem (MDPI AG, 2011)
The objective of the current study was to formulate ketorolac tromethamine-loaded elastic liposomes and evaluate their in vitro drug release and their ex vivo and in vivo transdermal delivery. Ketorolac tromethamine (KT), which is a potent analgesic, was formulated in elastic liposomes using Tween 80 as an edge activator. The elastic vesicles were prepared by film hydration after optimizing the sonication time and number of extrusions. The vesicles exhibited an entrapment efficiency of 73 ± 11%, vesicle size of 127.8 ± 3.4 nm and a zeta potential of −12 mV. In vitro drug release was analyzed from liposomes and an aqueous solution, using Franz diffusion cells and a cellophane dialysis membrane with molecular weight cut-off of 8000 Da. Ex vivo permeation of KT across pig ear skin was studied using a Franz diffusion cell, with phosphate buffer (pH 7.4) at 32 °C as receptor solution. An in vivo drug permeation study was conducted on healthy human volunteers using a tape-stripping technique. The in vitro results showed (i) a delayed release when KT was included in elastic liposomes, compared to an aqueous solution of the drug; (ii) a flux of 0.278 mg/cm2h and a lag time of about 10 h for ex vivo permeation studies, which may indicate that KT remains in the skin (with the possibility of exerting a local effect) before reaching the receptor medium; (iii) a good correlation between the total amount permeated, the penetration distance (both determined by tape stripping) and transepidermal water loss (TEWL) measured during the in vivo permeation studies. Elastic liposomes have the potential to transport the drug through the skin, keep their size and drug charge, and release the drug into deep skin layers. Therefore, elastic liposomes hold promise for the effective topical delivery of KT.